2016
DOI: 10.3109/07420528.2016.1171233
|View full text |Cite
|
Sign up to set email alerts
|

Morningness–eveningness and amplitude – development and validation of an improved composite scale to measure circadian preference and stability (MESSi)

Abstract: Measuring morningness-eveningness is an important aspect of individual differences because it is associated with many aspects of personality and health. The present study outlines recent advancements in the field of measurement and proposes an improved assessment of morningness-eveningness, such as the measurement of circadian amplitude, updating and reflecting new item developments, addressing the clock time based measures, the morning-biased items and the aspect of uni versus multidimensionality. Four studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
65
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(67 citation statements)
references
References 57 publications
1
65
0
1
Order By: Relevance
“…However, recent findings proposed the multidimensional structure of chronotype with two or more dimensions, such as that morningness and eveningness are separate dimensions and not just the two poles of one continuum, as well as the aspect of amplitude/stability (e.g., Putilov, Donskaya, & Verevkin, 2015;Randler, Díaz-Morales, Rahafar, & Vollmer, 2016;Scherrer, Roberts, & Preckel, 2016). Similarly, sleep quality was measured with a single item, and future studies might use a more elaborated measurement.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent findings proposed the multidimensional structure of chronotype with two or more dimensions, such as that morningness and eveningness are separate dimensions and not just the two poles of one continuum, as well as the aspect of amplitude/stability (e.g., Putilov, Donskaya, & Verevkin, 2015;Randler, Díaz-Morales, Rahafar, & Vollmer, 2016;Scherrer, Roberts, & Preckel, 2016). Similarly, sleep quality was measured with a single item, and future studies might use a more elaborated measurement.…”
Section: Discussionmentioning
confidence: 99%
“…First, the sample included workers who have been working for 3 to 8 years and consequently, future studies could benefit from using a wider age spectrum. Second, the use of other measures of circadian rhythm, such as rMEQ [172] and MESSi [35] could potentially overcome the issue of unevenly distributed chronotypes in our Chinese samples. Third, it would be interesting to examine cultural and environmental differences with respect to our results and findings, such as in an individualism-oriented country and using culturally modified cut-off criteria of chronotypes, as proposed by Kerkhof [173] and Caci et al [174], in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…These studies also revealed that most of the existing scales predominantly measure morningness. Some recent studies used circadian preference measures, which were based on a twodimensional conceptualization and accordingly assessed morningness and eveningness as two relatively independent dimensions (Lipnevich et al, in press;Scherrer et al, 2016;Putilov et al, 2015;Randler, Díaz-Morales, Rahafar, & Vollmer, 2016). Using confirmatory factor analyses, Scherrer et al (2016) and Randler et al (2016) demonstrated a good fit of models with morningness and eveningness as two separate dimensions of circadian preference.…”
Section: Measurement Of Circadian Preferencementioning
confidence: 99%
“…Some recent studies used circadian preference measures, which were based on a twodimensional conceptualization and accordingly assessed morningness and eveningness as two relatively independent dimensions (Lipnevich et al, in press;Scherrer et al, 2016;Putilov et al, 2015;Randler, Díaz-Morales, Rahafar, & Vollmer, 2016). Using confirmatory factor analyses, Scherrer et al (2016) and Randler et al (2016) demonstrated a good fit of models with morningness and eveningness as two separate dimensions of circadian preference. The two-dimensional conceptualization of circadian preference represents correlations with academic achievement in a more differentiated way as it allows to investigate the relation of morningness and eveningness with academic achievement, separately (e.g., Preckel et al, 2011).…”
Section: Measurement Of Circadian Preferencementioning
confidence: 99%
See 1 more Smart Citation